Predicting employee performance through extrinsic motivation: A conceptual model and empirical validation - Adi Mulyadi; Wawan Prahiawan; Ranthy Pancasasti; Didit Haryadi (Institute of Computer Science (IOCS), 2023)
An organization can only be successful with the help of its resources, especially its employees. Therefore, employees are the driving force that truly contributes to the sustainable success of the organization. Of course, this success can only be achieved with optimally performing employees. However, to maximize employee performance, strategies are needed to improve it, specifically to create an organizational culture on the part of employees so that it has an impact on performance. This research aims to identify how such strategies can improve employee performance. The method approach that the author uses is descriptive quantitative with associative. This research uses PLS-SEM based methodology. The population and sample in this study were marketing employees of PT Surya Madistrindo Serang Banten Indonesia totaling 151 respondents, all populations were drawn into the sample with saturated / total sample techniques. The results showed that work discipline, organizational culture, and extrinsic motivation can be optimized directly or indirectly through extrinsic motivation. To be able to improve employee performance can be done by improving work discipline and organizational culture directly or through extrinsic motivation.